Igra povijesti na razmeđi svjetova - povijest u kazalištu kraja Austro-Ugarske i početka Države/Kraljevine SHS / Ivica Baković - Baković, Ivica prevoditelj (Array, 2011)
This work analyses the status of plays with a historical theme and their performances during the dissolution of the Austro-Hungarian Empire, and the declaration of the new State of Slovenes, Croats and Serbs. The plays selected for this work are those that were on the repertoires of the national theatres in Ljubljana, Zagreb, Belgrade and Skopje.